Encapsulation Of Multiple Chips Led Module Using Computational Fluid Dynamic - Ibrahim, Muhammad Fauzan (Universiti Sains Malaysia, 2021)
The demand for light emitting diodes (LED) has risen significantly due to their advantages over fluorescent and incandescent light bulbs. LED lighting has low-power consumption, long-life, and ecologically friendly technology. Additionally, they are significantly more efficient, converting most energy to light and thus emitting less heat. A polymeric material that acts as a nonconductive material fills the space between the lens and the LED chip. Encapsulation is used to protect the device from mechanical forces that could weaken the connection. This research aimed to conduct a computational fluid dynamics simulation of the filling process for polymeric materials. According to rheology models, the viscosity affects this dispensing application. Hence, the effect of three different encapsulant materials with varying viscosities was investigated. The shape and motion of the encapsulant materials are predicted using ANSYS FLUENT's volume of fluid (VOF) multiphase modeling. The simulation result will be compared to previous research on LED encapsulation. As a result, the filling volume tends to overfill as the viscosity increases. Additionally, high viscosity materials have a higher void content than low viscosity materials. Additionally, it requires a longer filling time to accommodate the high viscosity material used in the encapsulation process.